Climate change and drinking water from Scottish peatlands: Where increasing DOC is an issue?. (15th December 2021) - Ferretto, Anna; Brooker, Rob; Matthews, Robin; Smith, Pete
Abstract: Increasing levels of dissolved organic carbon (DOC) have been detected in the last decades in water bodies of the Northern hemisphere, and climate change might fuel this rise. For drinking water reservoirs located in peatland catchments, already subjected to elevated amounts of DOC that needs to be removed, this might pose a further problem. Scotland is predicted to face warmer temperatures and a change in rainfall patterns, which will result in more frequent and severe summer droughts and in heavier winter precipitation. These conditions are not ideal for peatlands, which may undergo a drastic reduction in area. Using two bioclimatic envelope models (Blanket bog Tree model and Lindsay Modified model) that project blanket bog distribution in Scotland in the 2050s, we extracted the area of blanket bog that is at risk of loss. Assuming that part of the carbon stored in this area is likely to be lost, we calculated how much of it could be added to DOC in catchments that contain public drinking water reservoirs each year. This analysis is a first estimate of the risk for the provision of drinking water from peatlands in Scotland due to climate change. The aim is to identify the catchments that may face the highest consequences of future climates in terms of the concentration of DOC ([DOC]), where more sophisticated water treatments might be needed. Our results show a great variability among the catchments, with only a few being unaffected by this problem, whereas others could experience substantial seasonal increase in [DOC]. This highlights the necessity to frequently monitor DOC levels in the reservoirs located in catchments where the major problems could arise, and to take the necessary measures to reduce it. Given that peatland condition and vegetation cover play a fundamental role in influencing DOC losses, this study also offers an indication of where peatland restoration might be useful to counteract the projected DOC increase and bring the highest benefits in terms of safe drinking water provision. Highlights: Country-wide assessment of projected drinking water security in Scotland. Bioclimatic envelope models applied to Scottish blanket bogs. Impact of climate change on dissolved organic carbon (DOC) from peatlands. Few catchments not impacted, others will suffer a huge increase in DOC. Identified areas where to focus peatland restoration for future water security.